2019
DOI: 10.1093/jn/nxz087
|View full text |Cite
|
Sign up to set email alerts
|

Behavior Change Interventions Delivered through Interpersonal Communication, Agricultural Activities, Community Mobilization, and Mass Media Increase Complementary Feeding Practices and Reduce Child Stunting in Ethiopia

Abstract: Background Appropriate infant and young child feeding practices are critical for optimal child growth and development, but in Ethiopia, complementary feeding (CF) practices are very poor. Alive & Thrive (A&T) provided intensive behavior change interventions through 4 platforms: interpersonal communication (IPC), nutrition-sensitive agricultural activities (AG), community mobilization (CM), and mass media (MM). Objectives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
79
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(94 citation statements)
references
References 29 publications
4
79
0
5
Order By: Relevance
“…The rst arm of the study found an increase in the proportion of infants who were introduced to solid, semi-solid and soft foods (from 37.4-59.7%, P-value < 0.001) [58]. In contrast, the second arm of the study did not nd a signi cant improvement (from 58.7-61.3%, P-value > 0.05) [64].…”
Section: Risk Of Bias In Included Studiesmentioning
confidence: 90%
See 4 more Smart Citations
“…The rst arm of the study found an increase in the proportion of infants who were introduced to solid, semi-solid and soft foods (from 37.4-59.7%, P-value < 0.001) [58]. In contrast, the second arm of the study did not nd a signi cant improvement (from 58.7-61.3%, P-value > 0.05) [64].…”
Section: Risk Of Bias In Included Studiesmentioning
confidence: 90%
“…Three cluster randomised trials were assessed for risk of bias using the Cochrane RoB 2.0 tool. Overall, studies by Kang et al and Tariku et al judged as some concerns in the risk of bias [63,65], and the remaining study by Kim et al had a low risk of bias [64]. All cluster randomised trials had a low risk of bias in randomisation, missing data, and reporting of results.…”
Section: Risk Of Bias In Included Studiesmentioning
confidence: 95%
See 3 more Smart Citations